Impact of Influencers in the TikTok Application on Brand Awareness and Consumers Decision to Purchase Skincare Products - Sirilon, Apisara; Chairat, Janjira; Nuchmee, Thitima; Puengpae, Sirilux; Dansiri, Warapon (NIDA Business Journal, 2024)
This research study aims to study impact of influencers in the TikTok application on brand awareness and consumer purchasing decisions for skincare products. The sample group consisted of 400 people aged 18 years and over who were interested in ordering skincare products after being influenced by influencers on the TikTok application. The research tool was a questionnaire via Google form and the data was analyzed using the SPSS program to analyze basic statistics, multiple regression analysis and path coefficient analysis. The results of the study found that the influencer’s credibility factor and content marketing factor positively influence the brand awareness factor. Brand awareness also has a positive influence on consumers’ decision to purchase skincare products. Moreover, tests for indirect effects found that influencer’s credibility factors and content marketing factors positively influence consumers’ decisions to purchase skincare products, with the brand awareness factor as the intermediary variable. This study can be beneficial to entrepreneurs in choosing influencers to design media content that is appropriate for their own brands on social media platforms.